2007
DOI: 10.1080/10934520701418607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dry and living Sphagnum palustre moss samples in determining their biocumulative capability as biomonitoring tools

Abstract: Dry and living Sphagnum palustre moss samples were compared in parallel in order to study their biocumulative capability as biomonitoring tools. The two biomonitoring forms were used and compared to evaluate advantages and disadvantages of both preparation approaches and to choose the most suitable tool. The study was performed in an urban area to identify the main pollution sources. Cluster Analysis and Principal Components Analysis were used in order to identify specific element profiles attributed to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The PCA suggested, examining the scree plot, and considering Eigen Values greater than one suggested that two factors be extracted. The two factors extracted accounted for 94.5% of the variance, the parallel analysis resulted in the same conclusion [30]. The Kaiser-MeyerOlkin value was 0.62 (above the recommend .5) and Bartlett's test was significant, p<0.001.…”
Section: Exploratory Factor Analysissupporting
confidence: 54%
“…The PCA suggested, examining the scree plot, and considering Eigen Values greater than one suggested that two factors be extracted. The two factors extracted accounted for 94.5% of the variance, the parallel analysis resulted in the same conclusion [30]. The Kaiser-MeyerOlkin value was 0.62 (above the recommend .5) and Bartlett's test was significant, p<0.001.…”
Section: Exploratory Factor Analysissupporting
confidence: 54%
“…Moreover, this exposure system reduced the likelihood of producing hydric stress and improved the efficiency of retention of elements (Al-Radady et al 1993;Fernandez and Carballeira 2000;Couto et al 2004a;. Moreover, Szczepaniak et al (2007) argued that living mosses were a very useful tool in biomonitoring. If dry moss accumulates metal trace elements, chemometric (statistical) data treatment cannot identify in a reliable way the sources of pollutants.…”
Section: Resultsmentioning
confidence: 95%
“…Several papers have appeared stimulating methodological issues concerning a standardized implementation of active biomonitoring (Szczepaniak and Biziuk 2003;Szczepaniak et al 2007;Moreira et al 2005;Godinho et al 2008;Aničić et al 2009;Giordano et al 2009 among others). Selection and preparation of proper species, pre-exposure treatment, and vital state of the species, preparation of the transplants or the bags, method and duration of exposure of the samples, post-exposure treatments, analytical techniques and methods, and quality assurance are basic concepts in such an effort for a standardized methodology and for the harmonization of techniques (Ares et al 2012;Giordano et al 2013).…”
mentioning
confidence: 97%